Dissociable profiles of generalization/discrimination in the human hippocampus during associative retrieval. Issue 2 (30th December 2016) - De Shetler, Natalie G.; Rissman, Jesse
Abstract : When encountering stimuli that vary slightly from previous experiences, neural signals within the CA3 and dentate gyrus (CA3 DG) hippocampal subfields are thought to facilitate mnemonic discrimination, whereas CA1 may be less sensitive to minor stimulus changes, allowing for generalization across similar events. Studies have also posited a critical role for CA1 in the comparison of events to memory‐derived expectations, but the degree to which these processes are impacted by explicit retrieval demands is yet unclear. To evaluate extant accounts of hippocampal subfield function, we acquired high‐resolution fMRI data as participants performed a task in which famous names were used to cue the retrieval of previously paired images. Although both left CA3 DG and CA1 showed match enhancement effects, responding more to original paired images (targets) than to never‐before‐seen images (novels), the sensitivity of these subfields to stimulus changes and task demands diverged. CA3 DG showed a goal‐independent, yet highly specific, preference for previously encountered stimuli, responding equally strongly to targets and mispaired associates, while showing equally weak responses to close lures and novels. In contrast, recognition signals in CA1 were goal‐dependent (i.e., not evoked by mispaired associates), yet accommodating of subtle stimulus differences, such that close lures evoked comparable activity as targets. © 2016 Wiley Periodicals, Inc.